Pathologic Femur Fracture in an Immunocompetent Healthy Young Adult due to Acute Osteomyelitis - Evan R. J. Goyette; Natalia Georgantzoglou; Darcy A. Kerr; Yvonne Cheung; Eric R. Henderson; Konstantinos Linos (Hindawi Limited, 2023)
An immunocompetent 33-year-old woman presented with a pathologic femur fracture after one month of progressively worsening right thigh pain. Open biopsy demonstrated acute suppurative osteomyelitis despite the lack of clinical risk factors. The polymicrobial infection was successfully treated with three operative procedures and culture-specific antibiotic agents. Acute osteomyelitis, while an uncommon cause of pathologic fracture, must always be on the differential diagnosis, even when no obvious predisposing factors are present. When investigating for an infectious etiology in cases such as our own, considering immunodeficiency syndromes alongside the more typical causes of osteomyelitis is encouraged.